Spatiotemporal dynamics of C and N isotopic signature of zooplankton: a seasonal study on a man-made lake in the Mediterranean region. Issue 4 (8th October 2014) - Fadda, Amedeo; Rawcliffe, Ruth; Padedda, Bachisio Mario; Lugliè, Antonella; Sechi, Nicola; Camin, Federica; Ziller, Luca; Manca, Marina
<x content-type="archive" xml:space="preserve">Abstract</x> Reservoirs are subject to severe fluctuations in the water level from seasonal and interannual climatic variations, as well as abstraction for irrigation, hydropower, and drinking water. This can affect the matter and energy transfer through the food web, of which zooplankton is of crucial importance. We traced seasonal changes in the carbon and nitrogen stable isotope signatures of suspended particulate matter and crustacean zooplankton from a small Mediterranean reservoir. The δ13C and δ15N isotopic baseline signature of the lake varied seasonally, becoming more 13C-depleted and 15N-enriched in winter and less 13C-depleted and 15N-enriched values in the drier summer months, when external water inputs were negligible. Seasonal changes in the δ13C and δ15N SPM isotopic signature were well reflected in the herbivorous cladocerans. δ15N of the calanoid and cyclopoid copepods were at least 3‰ greater than for the herbivorous cladocera, suggesting their potential use as a food resource. δ13C of predatory copepods were also consistent with seasonal fluctuations in the δ13C SPM baseline, except during the heavy rains in early spring, when they were observably rich in lipids with a higher C/N ratio, suggesting that they had entered dormancy and were not actively feeding in the water column. This indicates the importance of taking into account not only the seasonality, but the community dynamics and trophic level of zooplankton taxa when interpreting stable isotope studies.